Au-Mo0. 1W0. 9O2. 72 double-plasmon nanoreactor as well as preparation method and application thereof
Through the Au-Mo0.1W0.9O2.72 dual-plasma nanoreactor loaded with Au nanoparticles on the Mo0.1W0.9O2.72 support, the problems of nitrogen adsorption activation and low light utilization in the existing photocatalytic ammonia synthesis technology were solved, and efficient photocatalytic nitrogen fixation and ammonia generation were achieved.
Patent Information
- Application Number
- CN202411747169.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In the existing photocatalytic ammonia synthesis technology, the light utilization rate of nitrogen adsorption activation and photocatalytic reactions are low, resulting in low ammonia synthesis efficiency, limiting the application and industrialization of the process.
Au-Mo0.1W0.9O2.72 biplasmic nanoreactor was used as a photocatalyst to generate thermally-rich electrons by loading Au nanoparticles on the Mo0.1W0.9O2.72 carrier, and the dual plasmon resonance coupling effect was used to improve the adsorption and activation of nitrogen and nitrogen reduction intermediates.
The activity of photocatalytic nitrogen fixation is significantly improved and efficient ammonia production is achieved. For example, under full spectrum light irradiation, the ammonia production rate is as high as 562.3 μmol/g/h.
Smart Images

Figure CN119657135A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysis technology, and specifically relates to an Au-Mo 0.1 W 0.9 O 2.72 A dual plasmon nanoreactor and its preparation method and application. Background Art
[0002] Ammonia is the basic raw material for fertilizers and industrial chemicals, and is also a clean energy carrier with high hydrogen storage. Therefore, the synthetic ammonia industry is of vital importance to the development of human society. Traditional thermal catalytic ammonia synthesis accounts for about 30% of the total ammonia synthesis. The Haber-Bosch method used consumes 1-3% of the energy released by global fossil fuel combustion, and also emits about 300 million tons of greenhouse gases each year. Therefore, the development of green, clean and efficient ammonia synthesis strategies has always been a cutting-edge topic and research hotspot. In 1977, Guth and Schrauzer first proposed to synthesize ammonia under mild conditions using TiO2 as a photocatalyst and nitrogen and water as raw materials. In recent years, the field of photocatalytic ammonia synthesis has attracted the attention of many researchers. In the process of photocatalytic ammonia synthesis, there are two main factors that limit the reaction. On the one hand, it is the adsorption and activation of nitrogen, one of the reactants, and on the other hand, it is the light transmission during the photocatalytic reaction. The low solubility and high bond energy of nitrogen hinder the adsorption and activation of nitrogen on the catalyst surface. The low light utilization rate and low solar energy conversion efficiency of traditional photocatalysts directly lead to low efficiency of photocatalytic ammonia synthesis, which seriously limits the scale-up and even industrial application of photocatalytic ammonia synthesis process. Therefore, the development of high-efficiency photocatalytic ammonia synthesis catalysts is the core. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the object of the present invention is to provide an Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor and its preparation method and application, the nanoreactor is based on Mo 0.1 W 0.9 O 2.72 As a carrier, Au nanoparticles are loaded on the surface and have good light response. Under light excitation, the hot electron-rich surface improves the adsorption and activation of nitrogen and nitrogen reduction intermediates, significantly enhancing the activity of photocatalytic nitrogen fixation.
[0004] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0005] A kind of Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor, based on Mo 0.1 W 0.9 O 2.72The carrier is loaded with 2-10wt% Au nanoparticles.
[0006] Preferably, the loading amount of the Au nanoparticles is 4-6wt%.
[0007] Au-Mo of the present invention 0.1 W 0.9 O 2.72 The dual plasmon nanoreactor has a dual plasmon resonance coupling effect, that is, the LSPR effect of metal nanoparticles is coupled with the SPR effect of non-metals. The hot electrons generated are concentrated in the nanoscale area near the surface, which can generate high energy and high local electromagnetic fields in a very small space, which is conducive to the interaction between hot electrons and surface adsorbed molecules and promotes the activation of inert molecules.
[0008] The present invention also provides the Au-Mo 0.1 W 0.9 O 2.72 The preparation method of the dual plasmon nanoreactor comprises the following steps: firstly dissolving a tungsten source and a molybdenum source in ethanol to obtain a tungsten-molybdenum mixed solution; synthesizing the tungsten-molybdenum mixed solution by solvent thermal synthesis to obtain molybdenum-doped tungsten oxide; then mixing and impregnating a chloroauric acid solution and molybdenum-doped tungsten oxide to obtain a precursor; and finally calcining the precursor in a reducing atmosphere to obtain Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor.
[0009] Preferably, the tungsten source is selected from one of tungsten pentachloride, tungsten hexachloride and tungsten hexacarbonyl; and the molybdenum source is molybdenum pentachloride.
[0010] Preferably, the solvent thermal temperature is 140-200° C. and the time is 12-24 hours.
[0011] Preferably, the concentration of the chloroauric acid solution is 10-50 mmol / L.
[0012] Preferably, the calcination process is: heating to 60-100°C at 2-10°C / min and maintaining for 0.5-1h, then heating to 200-240°C at 2-10°C / min and maintaining for 1-3h; the reducing atmosphere is a H2 / Ar mixed atmosphere.
[0013] The present invention also provides the Au-Mo 0.1 W 0.9 O 2.72 Application of dual plasmon nanoreactor for photocatalytic nitrogen fixation.
[0014] Compared with the prior art, the present invention has the following advantages:
[0015] Au-Mo of the present invention 0.1 W0.9 O 2.72 Dual plasmon nanoreactor, based on Mo 0.1 W 0.9 O 2.72 The Au-Mo nanoparticles are loaded on the surface and have good light response. The hot electron-rich surface under light excitation improves the adsorption and activation of nitrogen and nitrogen reduction intermediates, and significantly improves the activity of photocatalytic nitrogen fixation. For example, under full-spectrum light irradiation, without any sacrificial agent, the Au-Mo prepared in Example 1 0.1 W 0.9 O 2.72 The ammonia production rate is as high as 562.3 μmol / g / h. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 XRD spectra of samples prepared in Example 1 (AMWO) and Comparative Example 1 (WO);
[0017] Figure 2 The SEM images of the samples prepared in Example 1(a) and Comparative Example 1(b);
[0018] Figure 3 HAADF-STEM of the sample prepared in Example 1;
[0019] Figure 4 For Comparative Example 1 (WO 2.72 ), Comparative Example 2 (MoWO 2.72 ), Comparative Example 3 (Au-WO 2.72 ), Comparative Example 4 (CuWO 2.72 ) and Comparative Example 5 (LaWO 2.72 ) Photocatalytic nitrogen fixation performance diagram of the sample prepared;
[0020] Figure 5 The photocatalytic nitrogen fixation performance diagram of the samples prepared in Example 1 (AMWO) and Comparative Example 1 (WO);
[0021] Figure 6 UV-vis graphs of samples prepared in Example 1 (AMWO) and Comparative Example 1 (WO);
[0022] Figure 7 OCP diagrams of samples prepared in Example 1 (AMWO) and Comparative Example 1 (WO);
[0023] Figure 8 N2-TPD graphs of the samples prepared in Example 1 (AMWO) and Comparative Example 1 (WO). DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0025] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0026] Photocatalytic synthesis of ammonia:
[0027] Weigh 5 mg of catalyst powder and add it to 10 ml of ultrapure water. After dispersing under ultrasound for 10 minutes, transfer it to a reaction tube, evacuate the reaction tube, and backfill with ultrapure nitrogen. Repeat three times. Turn on the xenon light source under stirring conditions and continue irradiating with full-spectrum light for 1 hour. After the reaction is completed, centrifuge the mixture to obtain the supernatant, and filter it with a 0.22 μm water filter. The final clear solution is used to detect the ammonium ion concentration using an ion selective electrode and a colorimetric method.
[0028] Example 1
[0029] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved. Then, 1.25 ml of HCl solution (36 wt%) and 5 mg of MoCl5 were measured and mixed with the above solution and stirred for 30 min. The final mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and treated at 160 ° C for 16 hours. After cooling to room temperature, it was centrifuged, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C to obtain a light blue product MoWO 2.72 50mg MoWO 2.72 and 0.6 ml of 25 mM HAuCl4 were dissolved in 20 mL of saturated Ar water, stirred at room temperature for 120 min, and the solid was collected by centrifugation and dried at 60 ° C in vacuum. The solid was ground into powder and transferred to a porcelain boat and placed in a tube furnace. The temperature was raised to 80 ° C at 5 ° C / min and kept for 30 min, and then raised to 220 ° C at 5 ° C / min and kept for 120 min. The sample was cooled naturally and recorded as Au-Mo 0.1 W 0.9 O 2.72 , ICP-OES further confirmed that the loading amount of Au nanoparticles was about 5.5wt%.
[0030] like Figure 1 As shown, the X-ray diffraction (XRD) pattern confirms that MWO shows two strong diffraction peaks at 23.2° and 47.6°, corresponding to the standard WO 2.72The (010) and (020) crystal planes of (JCPDS-PDF#841516) do not have the characteristic peaks of molybdenum oxide crystals, indicating that there is no molybdenum oxide in the catalyst, that is, molybdenum exists in the form of elemental doping in tungsten oxide. In addition, the (111) crystal plane of Au (JCPDS-PDF#040784) is shown at 38.2°, confirming the presence of Au particles in the composite catalyst.
[0031] like Figure 2 As shown, Au-Mo 0.1 W 0.9 O 2.72 Scanning electron microscope (SEM) images of dual plasmon nanoreactors confirm that Au-Mo 0.1 W 0.9 O 2.72 The size of the medium carrier is about 15 nm with a narrow size distribution, and SEM characterization cannot observe the surface-loaded Au nanoparticles, proving that their size is small.
[0032] like Figure 3 As shown, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) reveals that Au-Mo 0.1 W 0.9 O 2.72 The morphological characteristics of the Au nanoparticles on the surface are shown in Figure 2. The average radius of the Au nanoparticles loaded on the surface is about 5nm, and they are regular spherical. The lattice fringes of the carrier and the loaded particles can be clearly identified by aberration-corrected annular dark-field scanning transmission electron microscopy. The carrier lattice spacing of 0.381nm is the lattice spacing of the typical tungsten oxide 010 crystal plane, and the lattice spacing of the Au nanoparticles is 0.231nm, which also corresponds to the 111 crystal plane of gold. In addition, in the magnified image, there are no obvious bright spots on the carrier, confirming that Au mainly exists in the form of nanoparticles.
[0033] Example 2
[0034] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved. Then, 1.25 ml of HCl solution (36 wt%) and 5 mg of MoCl5 were measured and mixed with the above solution and stirred for 30 min. The final mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and treated at 160 ° C for 16 hours. After cooling to room temperature, it was centrifuged, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C to obtain a light blue product MoWO 2.72 50mg MoWO 2.72and 0.3 ml of 25 mM HAuCl4 were dissolved in 20 mL of saturated Ar water, stirred at room temperature for 120 min, and the solid was collected by centrifugation and dried at 60 ° C in vacuum. The solid was ground into powder and transferred to a porcelain boat and placed in a tube furnace. The temperature was raised to 80 ° C at 5 ° C / min and kept for 30 min, and then raised to 220 ° C at 5 ° C / min and kept for 120 min. The sample was cooled naturally and recorded as Au-Mo 0.1 W 0.9 O 2.72 -2, and ICP-OES further confirmed that the loading amount of Au nanoparticles was about 2.8wt%.
[0035] Example 3
[0036] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved. Then, 1.25 ml of HCl solution (36 wt%) and 5 mg of MoCl5 were measured and mixed with the above solution and stirred for 30 min. The final mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and treated at 160 ° C for 16 hours. After cooling to room temperature, it was centrifuged, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C to obtain a light blue product MoWO 2.72 50mg MoWO 2.72 and 1.2 ml of 25 mM HAuCl4 were dissolved in 20 mL of saturated Ar water, stirred at room temperature for 120 min, and the solid was collected by centrifugation and dried at 60 ° C in vacuum. The solid was ground into powder and transferred to a porcelain boat and placed in a tube furnace. The temperature was raised to 80 ° C at 5 ° C / min and kept for 30 min, and then raised to 220 ° C at 5 ° C / min and kept for 120 min. The sample was cooled naturally and recorded as Au-Mo 0.1 W 0.9 O 2.72 -3, and ICP-OES further confirmed that the loading amount of Au nanoparticles was about 9.8wt%.
[0037] Comparative Example 1
[0038] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved, transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and treated at 160 ° C for 16 hours. After cooling to room temperature, it was separated by centrifugation, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C. The obtained sample was recorded as WO 2.72 .
[0039] Comparative Example 2
[0040] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved. Then, 1.25 ml of HCl solution (36 wt%) and 5 mg of MoCl5 were measured and mixed with the above solution and stirred for 30 min. The final mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and treated at 160 ° C for 16 hours. After cooling to room temperature, it was centrifuged, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C. The obtained sample was recorded as MoWO 2.72 .
[0041] Comparative Example 3
[0042] 100 mg W(CO)6 was mixed with 28.75 mL ethanol under vigorous stirring until the solid was completely dissolved, transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and treated at 160 ° C for 16 hours. After cooling to room temperature, it was separated by centrifugation, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C to obtain the product WO 2.72 50mg WO 2.72 and 0.6 ml of 25 mM HAuCl4 were dissolved in 20 mL of saturated Ar water, stirred at room temperature for 120 min, and the solid was collected by centrifugation and dried in vacuum at 60 °C. The solid was ground into powder and transferred to a porcelain boat and placed in a tube furnace. The temperature was raised to 80 °C at 5 °C / min and maintained for 30 min, then raised to 220 °C at 5 °C / min and maintained for 120 min, and cooled naturally. The obtained sample was recorded as Au-WO 2.72 .
[0043] Comparative Example 4
[0044] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved. Then, 1.25 ml of HCl solution (36 wt%) and 0.05 mmol of CuCl2 were measured and mixed with the above solution and stirred for 30 min. The final mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and treated at 160 ° C for 16 hours. After cooling to room temperature, it was centrifuged, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C. The obtained sample was recorded as CuWO 2.72 .
[0045] Comparative Example 5
[0046] 100 mg of W(CO)6 was mixed with 28.75 mL of ethanol under vigorous stirring until the solid was completely dissolved. Then, 1.25 ml of HCl solution (36 wt%) and 0.05 mmol of LaCl3 were measured and mixed with the above solution and stirred for 30 min. The final mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and treated at 160 ° C for 16 hours. After cooling to room temperature, it was centrifuged, washed three times with a mixture of ethanol and water in a volume ratio of 1:1, and dried in a vacuum oven at 100 ° C. The obtained sample was recorded as LaWO 2.72 .
[0047] The samples prepared in Comparative Examples 1, 2, 3, 4 and 5 were used for photocatalytic synthesis of ammonia. The results are as follows: Figure 4 Shown: WO 2.72 、MoWO 2.72 、CuWO 2.72 、LaWO 2.72 and Au-WO 2.72 The ammonia production rates of MoWO were 21.2 μmol / g / h, 261.3 μmol / g / h, 79.4 μmol / g / h, 46.8 μmol / g / h and 34.7 μmol / g / h, respectively. 2.72 The catalytic activity is obviously better than that of other comparative examples.
[0048] The samples prepared in Example 1 and Comparative Example 1 were used for photocatalytic synthesis of ammonia for 4 hours. Figure 5 Shown: Au-Mo 0.1 W 0.9 O 2.72 The dual plasmon nanoreactor has excellent photocatalytic nitrogen fixation performance and is significantly better than the supported catalyst. Under full-spectrum light irradiation, without adding any sacrificial agent, the ammonia production rate is as high as 562.3 μmol / g / h.
[0049] like Figure 6 As shown, Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor compared to WO 2.72 The catalyst enhances light absorption in the visible region and broadens light absorption in the near-infrared region, making Au-Mo 0.1 W 0.9 O 2.72 Has good full spectrum absorption.
[0050] like Figure 7 As shown, Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor compared to WO2.72 The catalyst has a good photocurrent response.
[0051] like Figure 8 As shown, Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor compared to WO 2.72 The catalyst has a stronger chemical adsorption for nitrogen.
Claims
1. Au-Mo 0.1 W 0.9 O 2.72 A dual plasmon nanoreactor, characterized in that: The Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor based on Mo 0.1 W 0.9 O 2.72 The carrier is loaded with 2-10wt% Au nanoparticles.
2. The Au-Mo according to claim 1 0.1 W 0.9 O 2.72 A dual plasmon nanoreactor, characterized in that: The loading amount of the Au nanoparticles is 4-6 wt %.
3. The Au-Mo according to claim 1 or 2 0.1 W 0.9 O 2.72 The preparation method of the dual plasmon nanoreactor is characterized in that: Firstly, a tungsten source and a molybdenum source are dissolved in ethanol to obtain a tungsten-molybdenum mixed solution; the tungsten-molybdenum mixed solution is subjected to solvent thermal synthesis to obtain molybdenum-doped tungsten oxide; Then, the chloroauric acid solution and molybdenum-doped tungsten oxide are mixed and impregnated to obtain a precursor; finally, the precursor is calcined in a reducing atmosphere to obtain Au-Mo 0.1 W 0.9 O 2.72 Dual plasmon nanoreactor.
4. The preparation method according to claim 3, characterized in that: The tungsten source is selected from one of tungsten pentachloride, tungsten hexachloride and tungsten hexacarbonyl; the molybdenum source is molybdenum pentachloride.
5. The preparation method according to claim 3, characterized in that: The solvent thermal temperature is 140-200° C. and the time is 12-24 hours.
6. The preparation method according to claim 3, characterized in that: The concentration of the chloroauric acid solution is 10-50 mmol / L.
7. The preparation method according to claim 3, characterized in that: The calcination process is: heating to 60-100°C at 2-10°C / min and maintaining for 0.5-1h, then heating to 200-240°C at 2-10°C / min and maintaining for 1-3h; the reducing atmosphere is a H2 / Ar mixed atmosphere.
8. The Au-Mo according to any one of claims 1 to 2 0.1 W 0.9 O 2.72 Au-Mo prepared by a dual plasmon nanoreactor or the preparation method according to any one of claims 3 to 7 0.1 W 0.9 O 2.72 The application of the dual plasmon nanoreactor is characterized in that: It is used for photocatalytic nitrogen fixation.
Citation Information
Patent Citations
Nanosheet-shaped molybdenum-doped tungsten trioxide with oxygen defect, and preparation method and application of nanosheet-shaped molybdenum-doped tungsten trioxide
CN111097406A
High-dispersion ruthenium-modified oxygen-defect-rich semiconductor photocatalyst as well as preparation method and application thereof
CN112403462A
Monodisperse metal-loaded tungsten oxide nanowire as well as preparation method and application thereof
CN114669307A
Mo-doped W18O49 photocatalytic material as well as preparation method and application thereof
CN116422322A
NITROGEN-DOPED TiO2 NANOPARTICLES AND THE USE THEREOF IN PHOTOCATALYSIS
US20210114893A1